Effect of Foot Massage on Pre- and Post Hysterectomy Anxiety - Zohre Maryami; Maryam Modarres; Simin Taavoni; Abbas Rahimi Foroushani (Tehran University of Medical Sciences, 2013)
Background & Aim: Hysterectomy is a common gynecologic surgery leading to great concerns in women. This study aimed to determine the effect of foot massage on anxiety level after hysterectomy.   Methods & Materials: In this double-group randomized clinical trial, 60 women undergone hysterectomy were selected using convenience sampling method and were randomly allocated into two intervention or control groups. Patients in the intervention group received foot massage three sessions during three consecutive days (every session lasted 20 minutes). In the control group, the researcher was only beside the women for 20 minutes. The Spilberger anxiety questionnaire was used to measure the anxiety level. Data were analyzed using repeated measures ANOVA and independent t-test.   Results: The mean of the anxiety score was not significantly different between the two groups before the intervention (P=0.21). After the intervention, there was significant difference between the two groups in the anxiety scores (P<0.001). There was also significant difference between the two groups in the anxiety scores one week after the surgery (P<0.001).   Conclusion: Foot massage can reduce anxiety in patients who underwent hysterectomy.